A study of self-similar vector fields in bianchi type III spacetime via Rif tree approach - Shakeel, Mehnaz; Khan, Jamshed; Rezapour, Shahram; Akhtar, Sumaira Saleem; Zahir, Hina; İnç, Mustafa (Iop Publishing Ltd, 2024)
In this study, we use the Rif tree approach to explore self-similar vector fi elds in Bianchi type III spacetime. This work adopt a computer-based method to transform symmetry equations into an involutive form that is simplified and divides the integration problem into multiple cases, each represented as a tree structure. In some cases, the metric functions are subject to particular constraints. These conditions allow one to solve the system of equations governing self-similar symmetries and provide explicit formulations for the metrics and their corresponding self-similar vector fi elds. This approach is novel in that it covers not only the analysis of the direct integration strategy but also some metrics that are practically relevant. For a detailed investigation of the created models, stability and physical importance are also considered.
Keywords: einstein field equations; bianchi type III spacetime; self similar vector fields; energy conditions